2020
DOI: 10.4028/www.scientific.net/kem.841.312
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Calcination Temperature on Metakaolin Characteristic Synthesized from Badau Belitung Kaolin

Abstract: The effect of Metakaolinization on the thermal and physicochemical properties of Badau Belitung kaolin is presented. Calcination of Badau Belitung kaolin indicated that kaolin was transformed to metakaolin at temperature above 500°C. The metakaolin was characterized using X-ray Diffraction (XRD), Fourier Transform Infrared (FT-IR) and Brunauer-Emmett-Teller (BET). The XRD diffraction pattern of the metakaolin was highly amorphous as a result of calcination effect on the raw kaolin. The FTIR spectra of the meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The previous studies have reported the determination of physical-chemical characteristics of "Badau Belitung kaolin" and their dehydroxylation effect during metakaolinization and metakaolinization on the specific surface area (Ulfiati et al, 2020a;Ulfiati et al, 2020b). The current study aims to observe the physicochemical properties and catalytical performance of ZSM-5 catalyst based on kaolin produced.…”
Section: Introductionmentioning
confidence: 94%
“…The previous studies have reported the determination of physical-chemical characteristics of "Badau Belitung kaolin" and their dehydroxylation effect during metakaolinization and metakaolinization on the specific surface area (Ulfiati et al, 2020a;Ulfiati et al, 2020b). The current study aims to observe the physicochemical properties and catalytical performance of ZSM-5 catalyst based on kaolin produced.…”
Section: Introductionmentioning
confidence: 94%
“…16 Furthermore, much effort has been expended to loading Ni and Mo onto the supports of ZSM-5 catalysts in order to boost their catalytic activity. 19 Earlier studies 20,21 evaluated the physical-chemical properties of Badau Belitung kaolin and their dihydroxyl meta-kaolinization on a specic surface area. The physicochemical properties and catalytic performance of the kaolin-based ZSM-5 developed for heavy distillate catalytic cracking were revealed in 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies 20,21 evaluated the physical–chemical properties of Badau Belitung kaolin and their dihydroxyl meta -kaolinization on a specific surface area. The physicochemical properties and catalytic performance of the kaolin-based ZSM-5 developed for heavy distillate catalytic cracking were revealed in 2022.…”
Section: Introductionmentioning
confidence: 99%